Analysis of the Financial Statements of PT. Sumber Alfaria Trijaya Tbk. to Assess the Company's Performance Before and During the Covid-19 Pandemic - Khrisna Sri Prihatin (MUAMALATUNA, 2023)
This study to assess the company’s performance financial uses a quantitative descriptive approach with the object of research on financial statements, where in this study uses four financial ratios, namely liquidity ratios, solvency ratios, profitability ratios and activity ratios for assess the company's performance. The results of the financial ratio analysis, the current ratio in 2018 was 1.15, in 2019, 1.2 and in 2020 it was 0.88. Quick ratio in 2018 was 0.50, in 2019 it was 0.55, and in 2020 it was 0.39. The debt to asset ratio in 2018 was 0.73, in 2019 it was 0.71 and in 2020 it was 0.70 while the debt to equity ratio in 2018 was 2.68, in 2019 it was 2.48 and in 2020 it was 2.40. Return on assets in 2018 was 3.0, in 2019 it was 4.7 and in 2020 it was 4.2. While the return on equity in 2018 was 11.10, in 2019 it was 16.54 and in 2020 it was 14.25 and total asset turnover in 2018 was 3.03, in 2019 it was 3.16 and in 2020 it was 3.03 and working capital growth in 2018 was 11.86, in 2019 it was 11.30 and in 2020 it was 10.44. From the results of the analysis, it shows that there is a decline in company performance during the pandemic.